KEPADATAN POPULASI DAN JENIS PAKAN KELASI (Presbytis rubicunda Muller 1838) DI KAWASAN ARBORETUM NYARU MENTENG, PALANGKA RAYA : Fouad Fauzi, Reni Rahmawati, Penyang - JHT, Admin (Jurnal Hutan Tropika, 2017)
ABSTRACK Nyaru Menteng arboretum is the genetics resources area that located at the Palangka Raya District, its wide namely 65.2 ha. In this area, there are many flora and fauna, including kelasi (Presbytis rubicunda), a species in danger that protected by law. At the Nyaru Menteng arboretum area, there are also the Re- introduction of Orang Utan Centre that managed by BOS. This research was aimed to know the kelasi population at the Nyaru Menteng arboretum area and to record some herbs and plants to be their foods. The research was conducted at the Nyaru Menteng arboretum area at 2017 using survey method to calculate the population of kelasi number and wide of their habitat. Research result showed that there one kelasi at January 2017 at three kelasi at April 2017 namely kelasi of male, female and young. Analysis result showed that the density of kelasi was 0.06 species ha-1. There is decrement kelasi at 2017 than 2007. Ten years ago, kelasi was detectabled namely 15 species with the density was 0.23 species ha-1. Some herbs and plants which to be food of kelasi i.e. jambuan (Syzgium cerinum), saga (Adenathera microsperma), singkong (Manihot utilisima), karet (Havea brasiliensis), nenas (Ananas comosus), kelakai (Stenochlaena ralustris), buah nangka (Artocarpus integra) and other fruits. Keywords: Density, food, kelasi, population